2002
DOI: 10.1046/j.1524-4741.2002.08603.x
|View full text |Cite
|
Sign up to set email alerts
|

Swelling, Numbness, Pain, and Their Relationship to Arm Function Among Breast Cancer Survivors: A Disablement Process Model Perspective

Abstract: The disablement process model proposed by Nagi in 1965 and subsequently expanded by Verbrugge and Jette was used heuristically to study the relationships among morbidities and arm/shoulder function limitations that breast cancer survivors experience in the period following treatment. A telephone survey was administered to 148 patients (67%) from among 222 breast cancer survivors who had undergone surgery in 1997 and 1998. Sixty-three percent of respondents reported experiencing some numbness, while 35% noticed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
1
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 35 publications
3
56
1
5
Order By: Relevance
“…34 Similarly, more than onethird of all patients with conventional axillary dissection after breast cancer surgery suffer persistent arm problems, which may substantially affect QOL. 2,3,35,36 In light of the strong interrelation between various symptoms, including fatigue, sleeping disorders, and pain, it is hard to judge whether interventions specifically aimed to reduce fatigue will also substantially improve QOL throughout a broad range of various domains or whether a combined approach is more effective. 25 However, it has been shown that patients whose fatigue improved reported substantially greater improvements in energy, ability to perform usual activities, and overall health.…”
Section: Discussionmentioning
confidence: 99%
“…34 Similarly, more than onethird of all patients with conventional axillary dissection after breast cancer surgery suffer persistent arm problems, which may substantially affect QOL. 2,3,35,36 In light of the strong interrelation between various symptoms, including fatigue, sleeping disorders, and pain, it is hard to judge whether interventions specifically aimed to reduce fatigue will also substantially improve QOL throughout a broad range of various domains or whether a combined approach is more effective. 25 However, it has been shown that patients whose fatigue improved reported substantially greater improvements in energy, ability to perform usual activities, and overall health.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the participants in our study declared that after mastectomy they could not do housework or work in the garden, and this situation made them feel empty and inadequate. Other studies have reported that women felt unable to carry out daily life activities such as shopping, cleaning the home, and hanging clothes (32)(33)(34). Women who cannot fulfill their role in life after undergoing a mastectomy may experience feelings of loss related to the things they used to do so easily.…”
Section: My Body Imagementioning
confidence: 99%
“…These publications report that in particular, shoulder flexion, abduction, and external rotation angles decreased, that patients' activities of daily living were restricted, and that their quality of life was adversely affected (14)(15)(16)(17).…”
Section: Effects Of Clinical Pilates Exercises On Patients Developingmentioning
confidence: 99%